Comparison of 6-mm versus 8-mm-tip cryoablation catheter for the treatment of atrioventricular nodal reentrant tachycardia in children: A prospective study - Tuzcu, Volkan; Gül, Enes Elvin; Karacan, Mehmet; Kamalı, Hacer; Çelik, Nida; Akdeniz, Celal (Springer, 2017)
Due to its safety profile, cryoablation (Cryo) for atrioventricular nodal reentrant tachycardia (AVNRT) is more commonly preferred over radiofrequency (RF) ablation in children in recent years. Recent studies demonstrated high long-term success rates comparable to radiofrequency ablation. The aim of this prospective study was to compare the efficacy and safety of an 8-mm-tip versus 6-mm-tip Cryo catheter in the treatment of AVNRT in children. A total of 125 consecutive patients over 10 years of age with AVNRT were included. EnSite system (St. JudeMedical, St Paul, MN, USA) was used to reduce or eliminate fluoroscopy. The acute procedural success was 100% in both groups. The prodecure duration for the 8-mm-tip group was shorter (151.6 +/- 63.2 vs. 126.6 +/- 36.7 min, p < 0.01, respectively). Fluoroscopy was used in only 7 patients. The mean follow-up duration was 14.6 +/- 8.4 months (median 13.5 months, min. 3 months and max. 27 months). The recurrence rate for AVNRT was also comparable between the two groups (6-mm tip: 9.6 vs. 8-mm tip: 8%). Cryo of AVNRT is a safe and effective procedure with comparable acute and mid-term follow-up success rates using 6-mm and 8-mm-tip catheters in children. In addition, procedure duration is shorter with an 8-mm-tip Cryo catheter.
WOS: 000405798800018
PubMed ID: 28612086
Keywords: Cryoablation; AVNRT; Catheter Tip; Recurrence